Strongly Convergence of Two Iterations For a Common Fixed Point with an Application - Mohamed Hasan, Zahra Mahmood; Abed, Salwa Salman (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this paper, we study some cases of a common fixed point theorem for classes of firmly nonexpansive and generalized nonexpansive maps. In addition, we establish that the Picard-Mann iteration is faster than Noor iteration and we used Noor iteration to find the solution of delay differential equation.